Committed Moderates and Uncommitted Extremists: Ideological Leaning and Parties' Narratives on Military Interventions in Italy. Issue 3 (22nd May 2021) - Curini, Luigi; Vignoli, Valerio
Abstract: Current research highlights that ideology decisively affects political contestation concerning peace and security operations in European countries. In particular, recent studies suggest that party preferences on this issue follow a curvilinear distribution along the left-right axis, delineating a conflict between moderate and extreme parties. However, the impact of this cleavage on the use of strategic narratives to either support or criticize these missions requires more attention. This article aims to fill this gap by employing seeded latent Dirichlet allocation, a semi-supervised automated text analysis method, to analyze parliamentary debates on Italy's most significant troop deployments between 1994 and 2013. We expect to find that while moderates express a supportive narrative aimed at justifying the use of force, extremists attempt to delegitimize military interventions. Accordingly, we hypothesize that moderate parties emphasize more on the multilateral and humanitarian framework of a mission, while extremist parties focus more on its military means. The empirical findings largely confirm our hypotheses. By means of its method and results, the article contributes both empirically and methodologically to the debate on the party politics of military interventions in Europe.